2023
DOI: 10.3390/ncrna9040045
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modifications and Novel Protein-Binding Sites in Pre-miR-675—Explaining Its Regulatory Mechanism in Carcinogenesis

Abstract: Pre-miR-675 is a microRNA expressed from the exon 1 of H19 long noncoding RNA, and the atypical expression of pre-miR-675 has been linked with several diseases and disorders including cancer. To execute its function inside the cell, pre-miR-675 is folded into a particular conformation, which aids in its interaction with several other biological molecules. However, the exact folding dynamics of pre-miR-675 and its protein-binding motifs are currently unknown. Moreover, how H19 lncRNA and pre-miR-675 crosstalk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Following chemical probing, both modified and un-modified RNA were reverse transcribed using specific primer complementary to the 3’ RNA cassette (Dey 2023) and Superscript II reverse transcriptase under error prone conditions as previously described (Smola et al 2015). The generated cDNA was purified using G50 column (GE healthcare) and subjected to second strand synthesis (NEBNext Second Strand Synthesis Module).…”
Section: Methodsmentioning
confidence: 99%
“…Following chemical probing, both modified and un-modified RNA were reverse transcribed using specific primer complementary to the 3’ RNA cassette (Dey 2023) and Superscript II reverse transcriptase under error prone conditions as previously described (Smola et al 2015). The generated cDNA was purified using G50 column (GE healthcare) and subjected to second strand synthesis (NEBNext Second Strand Synthesis Module).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple other direct and indirect targets that exert miR-4646-5p tumor-suppressive effects, such as the cytokines and chemokines GCSF and IL6, which have tumor-promoting functions, were also explored, providing a theoretical basis for the combined treatment of TNBC with miR-4646-5p and immunotherapy, such as checkpoint inhibitors. PremiR-675 is a miRNA expressed by H19 lncRNA, and its abnormal expression is associated with various diseases, such as cancer and cardiovascular and neurological disorders [ 16 ]. Furthermore, Dey’s research revealed that premiR-675 could fold into a typical stem–loop helical conformation and has binding sites for FUS, SRSF1, SRSF9, FXR2, LIN28B, and HUR proteins, which can be further used for structure-based drug design.…”
mentioning
confidence: 99%